How are smallholder households coping with and adapting to climate-related shocks in Doyogena climate-smart landscapes, Ethiopia? - Bonilla Findji, Osana; Ortega, Angelly; Eitzinger, Anton; Recha, John W.M.; Ambaw, Gebermedihin; Abera, Wuletawu; Tamene, Lulseged D.; Demeke, Getamesay; Desalegn, Mesfin; Mekonnen, Kindu; Radeny, Maren A.O.; Solomon, Dawit; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This synthesis presents an analysis of the results from the 2019 monitoring implemented as a contribution to Activity 1.2 Assessment of climate-smart agricultural options in the Doyogena Climate-Smart Village (CSV), in the context of the CCAFS-EU-IFAD grant reference 2000002575 for the research project “Building livelihoods and resilience to climate change in East & West Africa: Agricultural Research for Development (AR4D) for large-scale implementation of Climate-Smart Agriculture” led by the Alliance of Bioversity International and CIAT.